Indian Emigration Rules 1923 and Special Rules - Planning Commission (Planning Commission, 1952)
In any district in which the Central Government so directs, the Emigration Commissioner shall provide sufficient and proper accommodation in a suitable place for such intending emigrants as he may collect pending their production before a Magistrate and removal to the port of embarkation. The Emigration Commissioner shall inform the District Magistrate of the situation proposed by him for the place of accommodation and shall obtain his approval to such situation before the place is brought into use.
Special Rules
Special Rules